Entrepreneurship as a transition to the circular economy - Fernandes, Cristina I. (2023)
Given the challenges facing businesses and society in mitigating climate change, creating and supporting sustainable entrepreneurship is critical. However, the influence of National Systems of Entrepreneurship (NSEs) on the circular economy has not yet been studied. Our research studies the impact of NSEs on countries' circular economies while assessing the impact of the digital transition on this relationship. Using dynamic panel econometric techniques and by using various international databases, it was possible to assess the effect of NSEs on the circular economy. Furthermore, our analysis also allowed us to research how the impact of the digital transition may influence the relationship between NSEs and the circular economy. We achieve that countries with advanced NSEs achieve superior grades in their circular economy. We intend to add to the theoretical field by extending the knowledge of the relationship between NSEs and the circular economy. We also intend that the various actors in the surrounding environment who enhance entrepreneurial activities, realize that entrepreneurship is a fundamental component, within the system to which it belongs, for achieving the circular economy.